A New Entity: Extrahepatic Undifferentiated Embryonal Sarcoma, Cytology as an Accurate Method of Diagnosis- A Rare Case Report - Nupur Rastogi (Research Developments in Medicine and Medical Science Vol. 3, 2023)
Undifferentiated embryonal sarcoma, a rare malignant mesenchymal neoplasm that mostly affects children and teenagers, has been documented in the liver. Since this illness was initially characterized in 1978, there have been 260 instances that have been identified as developing in the liver [1]. The pathophysiology of it is yet unknown. A 9 year old female presented with upper abdominal dull pain. The ultrasound and CT scan revealed normal liver architecture, with the liver pushed upwards due to compression by a tumor emerging in the retroperitoneum. Based on cytomorphology and confirmed by histopathology and immunohistochemistry markers, a diagnosis of Extrahepatic Undifferentiated Embryonal cell sarcoma was made which is the FIRST case to the best of my knowledge.